Temporal variation in seed quality of Indian spinach preserved in different containers (International Journal of Agricultural Research, Innovation and Technology, 2016)
The experiment was conducted to investigate the seed quality of Indian spinach for three months stored at different containers (Plastic pot, polythene bag and cloth bag) during 2013-2014 at Seed Technology Laboratory of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU), Gazipur. The initial moisture content of the seed was 9.89% with 75.00% germination. However, after two months, the seed had a different range of increased moisture content with reduced germination percentage depending upon the packing materials. Among the three containers, seeds stored at cloth bag absorbed more moisture (14.36%) from surrounding atmosphere followed by the moisture content, 12.67% and 11.50% of polythene bag and airtight plastic pot, respectively. Seeds stored at plastic pot, polythene bag and cloth bag exhibited 65.00, 64.00 and 50.00 per cent germination, respectively. Similarly, the fresh weight and dry weight of seedling and seedling vigor were also decreased. The seeds of plastic pot were good in term of germination capacity, fresh and dry weight and vigor index in comparison to those stored at cloth bag and polythene bag.Int. J. Agril. Res. Innov. & Tech. 5 (2): 51-57, December, 2015